Comparison of warm up protocols of high class male and female weightlifters - Charniga, A. (EWF Scientific Magazine, 2015)
Over the years a number of papers have been devoted to the weightlifter`s warm up for competition. Some of this information is more than 50 years old. However, in the interim there have been a number of changes to the technical rules of weightlifting competitions. For instance, there are now two competition exercises instead of three, two minutes instead of three to prepare if an athlete follows himself/herself for the next attempt on the platform, and one minute instead of two minutes to begin lifting the barbell on the platform after the athlete has been called. However, without question, the most dramatic change to the weightlifting program over past 50 years has been the inclusion of women weightlifters. The question as to whether there are, or for that matter need be, different warm up protocols for women weightlifters has not received any attention. Data collected at the 2008 Olympics provided the impetus to look into this question. The specific warm up loading of the four Chinese female gold medalists in Beijing represented a substantial departure for what is widely considered to be a reasonable competition warm up protocol for any sport!